Factibilidad para la creación de una microempresa dedicada a la fabricación y comercialización de vestidos de niñas, en la ciudad de Santo Domingo, año 2015 - Zambrano Suárez, Ana Libeth (2015)
The research was established to study the feasibility of creating a micro manufacturing and marketing of garments in Canton Santo Domingo, through a survey and analysis of supply and demand through the study of market and making a technical and financial to analyze the feasibility, location and size of investment study. In the absence of a place to find all kinds of dresses for girls in the city of Santo Domingo, it was necessary to introduce a proposal to strengthen the market in the textile field. Through economic study location, location macro and micro location of the company and established; its organizational structure prior to the start of its textile activities. Through economic and financial analysis of investment profitability which was established by calculating the various fixed and variable costs was found, taking into account factors such as raw materials, direct labor, indirect labor prays overhead for the constitution of the company and sales by revenue projection. Revenues are projected at the IRR and NPV analysis are very important tools to reach a conclusion in favor or against the investment, it was determined that a rate of 304% is obtained off so you have a period of capital recovery in less than a year. On the cost / benefit ratio of the project profitability and found that for every dollar of investment gain of $ 1.12 is obtained.